CONGENITAL HYDRONEPHROSIS: PROBLEMS IN DIAGNOSIS AND MANAGEMENT - Hutasoit, Yonas Immanuel; Wahyudi, Irfan; Rodjani, Arry (Indonesian Journal of Urology, 2010)
Objective: To evaluate problems in diagnosis and management of congenital hydronephrosis. Material & methods: This study was retrospective. Data was collected from medical records of patients with congenital hydronephrosis, which were hospitalized or went to urologic outpatient clinic at Ciptomangunkusumo Hospital from January 1999 to December 2008 and Harapan Kita Maternal and Pediatric Hospital from January 2004 to December 2008. Data was analyzed with SPSS programme version 13.0. Statistical analysis was performed to find the relationship between age at diagnosis and kidney function (Mann-Whitney test) and between age at diagnosis and nephrectomy rate (Chi-Square test). Results: There were 15 patients who presented because of antenatal diagnosis. Of the 145 patients, we could collect antenatal history only from 63 patients.  Obstetricians provided antenatal care in 56 out of 63 patients. Antenatal ultrasound was performed in only 59 out of 63 patients and only 44,07% (26 patients) with hydronephrosis was detected antenatally. Eleven out of 26 antenatally diagnosed patients came to our clinic at a later age. Three standard studies (postnatal ultrasound, voiding cystourethrogram, and renal scintigraphy) were performed only in 12 out of 145 patients (8,27%). Ultrasound was performed in 108 patients (74,5%), voiding cystourethrogram in 79 patients (54,5%), and renal scintigraphy in only 26 ptients (17,9%). The suggested management was conducted in 115 patients; operative management in 95 patients (82,61%) and conservative treatment in 20 patients (17,39%). The most common operative procedures were ureteroneocystostomy, pyeloplasty, nephrectomy, and posterior urethral valveablation. Mean serum creatinine in below 12 months old group and above 12 months old group was 0,78±0,93mg/dl dan 1,03±0,88 mg/dl respectively(p<0,05). There was no significant difference in nephrectomy rate in both age groups (p>0,05). Nephrectomy was performed in 16 patients, with the most common indication was grade IV hydronephrosis with thin parenchyma in 11 patients (68,75%) and the most common etiology was UPJ obstruction in 10 patients (62,5%). We can only collect follow up data from 73 out of 115 managed patients (63,48%). Urinalysis, ultrasound/voiding cystourethrogram, and renal function studies were not routinely conducted during follow up. Conclusion: The management of congenital hydronephrosis in Indonesia needs improvements in antenatal care standards, particularly obstetric ultrasound, to improve early detection of congenital hydronephrosis. Better education for parents about the importance of follow up is needed, especially for antenatally diagnosed patients. A consensus regarding diagnostic tools used in managing congenital hydronephrosis must be established among urologists, pediatricians, and radiologists.